2013
DOI: 10.1017/s1368980013001481
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring salt and iodine intakes in Dutch adults between 2006 and 2010 using 24 h urinary sodium and iodine excretions

Abstract: Objective: To monitor the effectiveness of salt-reduction initiatives in processed foods and changes in Dutch iodine policy on Na and iodine intakes in Dutch adults between 2006 and 2010. Design: Two cross-sectional studies among adults, conducted in 2006 and 2010, using identical protocols. Participants collected single 24 h urine samples and completed two short questionnaires on food consumption and urine collection procedures. Daily intakes of salt, iodine, K and Na:K were estimated, based on the analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 21 publications
2
30
1
1
Order By: Relevance
“…Therefore, considering that deficiency or excess of iodine is detrimental and that iodine sufficiency depends on adequate nutritional ingestion, strategies for the diagnosis and intervention of iodine insufficiency, or excess, are clearly feasible and must be implemented. There is need for ongoing monitoring of iodized salt in order to prevent excess as well as insufficient iodine nutrition, and will be essential to coordinate interventions designed to reduce population sodium intake with salt iodization programs in order to maintain adequate levels of iodine nutrition as salt intake declines (3,26).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, considering that deficiency or excess of iodine is detrimental and that iodine sufficiency depends on adequate nutritional ingestion, strategies for the diagnosis and intervention of iodine insufficiency, or excess, are clearly feasible and must be implemented. There is need for ongoing monitoring of iodized salt in order to prevent excess as well as insufficient iodine nutrition, and will be essential to coordinate interventions designed to reduce population sodium intake with salt iodization programs in order to maintain adequate levels of iodine nutrition as salt intake declines (3,26).…”
Section: Discussionmentioning
confidence: 99%
“…One estimated 24-h sodium excretion on the assumption that 45% of the sodium was excreted in the timed 12-h specimen (107). Of the studies that collected 24-h urine, only one (59) reported using a factor (95%) to adjust the estimate of intake for the percentage of sodium lost through sweat or stool.…”
Section: Current Aproaches To Assess Sodium Intake Through Urine Biommentioning
confidence: 99%
“…No two definitions for completion of 24-h urine collection were exactly the same. In relation to potential overcollection, in one study (59), participants were excluded if they reported collecting specimens outside the 24 hours. In two (20, 123), collection start and stop were supervised.…”
Section: Current Aproaches To Assess Sodium Intake Through Urine Biommentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, mild iodine deficiency was present in this part of The Netherlands (33,34). Currently, the iodine status of this population is considered to be adequate (35,36). Approval to conduct the study was obtained from the Institutional Review Board.…”
Section: Study Participantsmentioning
confidence: 99%